Dissection of a circulating CD3+CD20+ T cell subpopulation in patients with psoriasis. (6th March 2018) - Niu, J; Zhai, Z; Hao, F; Zhang, Y; Song, Z; Zhong, H
Summary: CD3 + CD20 + T cells are a population of CD3 + T cells that express CD20 and identified in healthy donors and autoimmune diseases. However, the nature and role of these cells in patients with psoriasis remain unclear. In this study, we aimed to investigate the level, phenotype, functional and clinical relevance of CD3 + CD20 + T cells in the peripheral blood of patients with psoriasis. We found that a small subset of CD3 + T cells expressed CD20 molecule in the peripheral blood of patients with psoriasis, and their levels were similar to those in healthy donors. Circulating CD3 + CD20 + T cells in patients with psoriasis were enriched in CD4 + cells and displayed an activated effector phenotype, as these cells contained fewer CD45RA + -naive and CCR7 + cells with increased activity than those of CD3 + T cells lacking CD20. In addition, compared with healthy donors, circulating CD3 + CD20 + T cells in patients with psoriasis produced more cytokines, interleukin (IL)-17A, tumour necrosis factor (TNF)-α and IL-21, but not IL-4 and IFN-γ. Furthermore, a significantly positive correlation was found between the levels of IL-17A, TNF-α and IL-21-production CD3 + CD20 + T cells with Psoriasis Area and Severity Index scores. Our findings suggest that CD3 + CD20 + T cells may play a role in the pathogenesis of psoriasis. Graphical Abstract: